External Barriers to Political Freedom from the Quran’s Point of View - Seyed Kazem SeyedBagheri (Journal of Islamic Political Studies, 2019)
Political freedom has faced internal and external barriers over time. This study aims to investigate external barriers to political freedom, approaching to Quran with the question that, what the external barriers to political freedom are that manifest themselves in the political and social arenas. It also stresses the assumption that the external barriers to political freedom must be observed within their oppressive scope with its specific principles, and counter forces to freedom, in addition to the internal barriers to political freedom. Those counter forces, which are regarded as freedom barriers include the Taghuts (Dictators), Mostakbers (arrogant rulers), aristocrats, the opulent, scholars. Hence, we set this question forth from the Quran: what the external barriers to human freedom are that often appear in political and social forms. Employing a local method of discretional interpretation and adopting a Quranic perspective, the study innovates in that it investigates external barriers to political freedom including the role of oppressive structure, fabricated rules together with the role of people and Taghuts.